Conservative treatment of tendinopathies of upper limbs in occupational health: a literature review - Sartorio, Francesco; Garzonio, Fabiola; Vercelli, Stefano; Bravini, Elisabetta; Ruella, Carolina; Maglio, Roberto; Cisari, Carlo; Ferriero, Giorgio (La Medicina del Lavoro, 2016)
Background: In the last few years, the incidence of upper limbs tendon injuries has seen a dramatic increase among workers. Conservative treatment is the first choice to relieve symptoms, allowing a safe return to work. However, the scientific evidence of its efficacy is widely debated. Objective and methods: Research and literature review on the efficacy of conservative treatment of upper limbs tendon injuries in occupational settings. Results: A total of 271 references were found on Medline and Embase up to May 2015. 116 papers were excluded, 155 articles were included and the full text read. Conclusions: After a timely diagnosis, a prompt start of the rehabilitation programme and a limitation of complete rest are useful to relieve pain, increase functionality and reduce work absenteeism in the long term. Conservative treatment combinations, such as manual therapy, specific exercises focused on increasing flexibility and muscle strength and specific-gesture training, achieves more significant results than a single isolated treatments. Currently, there is no strong scientific evidence to support prolotherapy and Platelet-Rich Plasma (PRP). However, current promising results will encourage further studies. Awareness among both employers and employees about prevention and risk factors should be enhanced.